AL-FĀRĀBĪ ET LA SCIENCE DES UṢŪL AL-FIQH. Issue 1 (March 2017) - Mensia, Mokdad Arfa
Abstract: It is known that Fārābī, in his political program, assumes philosophically some Islamic sciences like kalām and fiqh . Focusing here on the case of the fiqh and in the limits of his K. al-Milla, we try to establish correspondences between his theory of legislation and references to historically attested sciences. Our purpose is to show that he was able to articulate fiqh to the political science through an undeclared use of ʿilm uṣūl al-fiqh (science of principles of juridical science). He empties this science of its own material and preserves its form in order to fill it with philosophical material. This contributes to clear up his conception in this book of the shift from the voluntary universal to the particular. This shift is governed by a set of formal rules. These guidelines, which are rather deliberative, take place as a subject matter of the political science, alongside with universals, its classical subject matter. We think that these formal rules are borrowed from this typical Islamic science whose subject matter is the study of principles and rules governing the inference, from their sources, of particular legal status, the subject matter of fiqh . If, from the strict philosophical point of view, political science provides the sources or foundations from which are inferred the original and primary legislation initiated by the founder of the religion ( al-milla ), as well as the derived and secondary one elaborated by his successors, the methodological part of this Islamic science would be the equivalent to the general prescriptions necessary for the application of universals so that concrete cases can be determined. For this purpose, Fārābī borrows willingly from the famous Shāfiʿī's Risāla, the prototype of the treatises in uṣūl al-fiqh . Résumé: Il est un fait notoire: dans son programme politique, Fārābī prend philosophiquement en charge certaines sciences islamiques, telles que le kalām et le fiqh . En mettant l'accent sur le fiqh et en se limitant à son K. al-Milla, on tente ici de faire correspondre à sa théorie de la législation des références à des sciences historiques. Il s'agit de montrer que s'il a pu articuler le fiqh à la science politique, c'est moyennant un recours inavoué à ʿilm uṣūl al-fiqh (science des principes de la science juridique), dont il évacue la matière propre, ne gardant que la forme de cette discipline et la remplissant d'un matériau philosophique. Cela rend compte, au moins en partie, de la conception, exposée dans ce livre, du passage de l'universel au particulier dans les choses de la volonté, passage régi par un ensemble de règles formelles. Ce dispositif de nature assez délibérative, vient prendre sa place comme objet de la science politique, à côté des universaux, objet classique de cette science architectonique. Nous pensons que l'idée de ces règles formelles est empruntée à cette science typiquement islamique dont l'objet est l'étude des principes et des règles qui régissent l'inférence des dispositions légales particulières, objet du fiqh, à partir de leurs sources. Si, philosophiquement, la science politique pourvoit aux sources ou fondements dont sont inférées aussi bien la législation originelle ou primaire (celle de l'instaurateur de la religion, milla ) que la législation dérivée ou secondaire (celle de ses successeurs), la partie méthodologique de la science islamique serait l'équivalent des prescriptions générales nécessaires à l'application des universaux pour que des cas concrets puissent être déterminés. À cet effet, Fārābī fait volontiers des emprunts à la fameuse Risāla de Shāfiʿī, prototype des traités dans la science des uṣūl al-fiqh .